The Mental Image of Saudi society among International Students from the perspective of communication and culture - Al-Shihri, Ahmed Jaber (Journal of Humanities & Social Sciences, 2019)
This study aims to identify the mental image of international students from the perspective of communication and culture. The researcher used the descriptive approach and the questionnaire as a study tool on a sample of 470 students. The comprehensive survey method was applied to 345 respondents representing the international postgraduate students at King Saud University at the first semester of the 1438-1439 AH academic year, The most important results of this study include the following. The Internet is the preferred means used to search for answers to enquiries about the culture of the Saudi society in addition to the fact that most students visited various areas of the Kingdom and got to know something about the culture, which would strengthen the students’ mental image about the Kingdom and its culture. The difficulties faced by international students include mobility, communication and language barriers, and time shortage to learn more about the culture of the society, The study most important recommendations include the need to combine efforts of academic and cultural and social institutions in the Kingdom to acquaint international students with different cultural activities and to overcome the difficulties they face in communicating with the Saudi community, such as transportation and language difficulties and the availability of specialists with social and cultural expertise who realize how to deal with international students and help them form a clear mental image regarding the culture of Saudi society.
Keywords: mental image; Saudi society; communication; culture